Kinship and association do not explain vocal repertoire variation among individual sperm whales or social units - Konrad, Christine M.; Frasier, Timothy R.; Rendell, Luke; Whitehead, Hal; Gero, Shane (Animal Behaviour, 2018)
Vocal learning often results in distinct dialects among individuals or groups, but the forces selecting for these phenomena remain unclear. Female sperm whales, Physeter macrocephalus, and their dependent offspring live in matrilineally based social units, and the units associate within sympatric clans. The clans have distinctive dialects of codas (patterns of clicks), as do, to a lesser extent, the units within clans. We examined the similarity of coda repertoires of individuals and units from the eastern Caribbean and related these to patterns of kinship and social association. Similarity in coda repertoires was not discernibly correlated with close kinship or association rates for either individuals or units (matrix correlation coefficients